Heavy metals in fish and its association with autoimmunity in the development of juvenile idiopathic arthritis: a prospective birth cohort study - Erik Kindgren; Carlos Guerrero-Bosagna; Johnny Ludvigsson (BMC, 2019)
Abstract Background The etiology of Juvenile Idiopathic Arthritis (JIA) is poorly understood. The purpose of this study was to examine the possible influence of early nutrition on later development of JIA. Methods In a population-based prospective birth cohort of 15,740 children we collected nutritional data, including fish consumption, and biological samples during pregnancy, at birth and at different ages. 16 years after study inclusion we identified 42 children with JIA, of whom 11 were positive for Antinuclear Antibodies (ANA). Heavy metals were analysed in cord blood of all 42 JIA patients and 40 age and sex-matched controls. A multivariable logistic regression model, adjusted for relevant factors, was used as well as Mann-Whitney U-test. Results Fish consumption more than once a week during pregnancy as well as during the child's first year of life was associated with an increased risk of JIA (aOR 4.5 (1.95-10.4); p < 0.001 and aOR 5.1 (2.1-12.4) p < 0.001) and of ANA-positivity (aOR 2.2 (1.4-3.6); p = 0.002 and p < 0.001). Concentrations of Al, Cd, Hg and Li in cord blood were significantly higher in the JIA-group than in controls. The ANA-positive, all of whom had consumed fish >once/week their first year, had significantly higher concentrations of Al (p < 0.001), Cd (p = 0.003), and Li (p < 0.001) in cord blood than controls. Frequency of fish consumption correlated with concentrations of Cd (p = 0.003), Li (p = 0.015) and Hg (p = 0.011). Conclusions Moderate exposure to heavy metals, associated with fish consumption, during pregnancy and early childhood may cause effects on the immune system of the offspring, resulting in ANA positivity and JIA.